Enhancing Academic Writing Achievement Through Structured Peer Feedback and Self-Esteem Support in Hybrid EFL Learning - Burhan, Kristian; Amsa, Helfany; Astuti, Indri; Franchisca, Sherly (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
Despite the increasing use of peer feedback to improve EFL students’ academic writing, limited research has examined how self-esteem shapes students’ engagement with feedback and writing achievement in hybrid learning environments. Existing studies have largely treated these variables separately, leaving a limited understanding of their integrated contribution to writing development. This study aims to examine the effects of structured peer feedback on EFL university students’ academic writing achievement and to explore the relationship between self-esteem and engagement in peer feedback activities. Using a sequential explanatory mixed-method design, this study involved 64 undergraduate students at Universitas Ekasakti, Indonesia. Participants were assigned to an experimental group receiving structured peer feedback and a control group receiving conventional lecturer-centered feedback. Data were collected through an analytical writing rubric, the Rosenberg Self-Esteem Scale (RSES), peer feedback records, questionnaires, and semi-structured interviews. The findings revealed that the experimental group demonstrated significantly greater improvement in academic writing, particularly in content (Mean difference = 2.89, p < 0.001) and organization (Mean difference = 2.49, p < 0.001). Self-esteem was positively associated with final writing performance (r = 0.54), feedback quantity (r = 0.47), and feedback uptake (r = 0.51). Qualitative findings further showed that structured peer feedback promoted metacognitive reflection, collaboration, and writing confidence, although some students perceived online feedback interactions as emotionally distant. This study contributes to the literature on EFL writing and hybrid learning by demonstrating that peer feedback operates not only as a cognitive mechanism but also as a socio-emotional process shaped by students’ affective readiness. The findings imply that attention to students’ self-esteem and emotional readiness during feedback practices can strengthen student engagement and improve academic writing outcomes in technology-mediated learning environments.